Analysis of the Role of CPP-ACPF Paste in Combination with Aqueous Extracts of Propolis to Improve Enamel Roughness after Demineralization Challenge - Mayada Kashmoola; Aisha A. Qasim (University of Mosul, College of Dentistry, 2022)
Aims: This study aims to evaluate the combined efficacy of aqueous extracts of propolis and Fluoridated Casein Phosphopeptide-Amorphous Calcium Phosphate (CPP.ACPF) paste or Minimal Intervention (MI) paste plus on improving enamel surface roughness after demineralization challenge. Materials and methods: A total of (75) posterior wisdom teeth were used in the study. Enamel blocks were prepared and divided into five groups randomly, the teeth in all groups were subjected to demineralization cycle and then treated with: Sinjar's aqueous extract of propolis (AEP)-MI paste plus cream n. (15), Sulaymaniah's AEP-MI paste plus cream n. (15), Duhok's AEP-MI paste plus cream group n. (15), control positive group of MI paste plus alone n. (15), and control negative group of artificial saliva alone n. (15). The Roughness of enamel blocks was measured using a profilometer machine at baseline, after demineralization cycle and finally after the treatment protocol.Results: There were statistically high significant differences among study groups after the demineralization cycle and there was an increase in surface roughness in all groups after demineralization, but the least elevation in surface roughness belonged to a mixture of Sulaymaniah's aqueous extract of propolis with MI past plus followed by Duhok's aqueous extract of propolis with MI past plus group after treatment protocol. Statistically, there were high significant reductions in surface roughness in all groups after the remineralization except in an artificial saliva group. Conclusions: Combination CPP-ACPF Paste with Aqueous Extracts of Propolis reducing enamel's roughness and increasing resistance to demineralization.